Introducing RDA : a guide to the basics - Oliver, Chris, 1951-; American Library Association (Chicago : American Library Association, 2010)
Practical advice for catalogers and library administrators on how to make the transition from the Anglo-American cataloging rules (AACR) to Resource description and access (RDA).
What is RDA? -- RDA and the international context -- FRBR and FRAD in RDA -- Continuity with AACR2 -- Where do we see changes? -- Implementing RDA -- Advantages, present and future.
'ALA Editions special reports.'
Includes bibliographical references (p. 105-109) and index.
Keywords: Resource description & access; Anglo-American Cataloguing Rules; Descriptive cataloging -- Standards; Cataloging -- Standards